INFLUENCE OF ACCEPTANCE AND COMMITMENT THERAPY ON THE FAMILY’S BURDEN IN TREATING PEOPLE WITH MENTAL DISORDERS - I Putu Gde Yudara Sandra Putra; Noor Hamdani; Lilik Supriati (NurseLine Journal, 2017)
Indonesia has more than one million people with mental disorders spread in each province. Treatment for people with schizophrenia is not only done in the hospital alone, but it will be continued after returning to the family. Families who are not able to adapt to the patient's care problem will consider the problem as a burden by the family. Acceptance and Commitment Therapy (ACT) is one of therapy that aims to teach the individual to be aware and use a new perspective in thinking to face a problem. This research aimed to know the effect of ACT on the burden felt by the family in caring for the patient mental disorders. The design used in this research was Quasi-Experiment Pre-Post Test With Control Group. The numbers of samples in this study were 24 people divided into two groups. The independent variable in this study was ACT therapy while the dependent variable was the burden felt by the family. Data analysis in this research use t-test and linear regression. The results showed no significant difference in the control group after getting health counseling (p = 1.000). In the treatment group showed significant difference after getting health education and ACT (p = 0.000). There was a significant difference between intervention and control group (p = 0.000). The result of linear regression test showed that age factor and ACT therapy had an effect of 57.1% to the family burden. Families are expected to be more flexible to face problems found when treating people with mental disorders at home.